Contextual culpability: How drinking and social context impact sentencing of violence - Lightowlers, Carly (Criminology & criminal justice, 2022)
The controversial effect of intoxication on sentencing outcomes has received renewed attention with a series of new empirical studies. However, these studies have relied on survey data that conflate alcohol and drug intoxication and miss pertinent contextual features of the offence. This article explores how alcohol intoxication, and its social context, impact sentence outcomes for violent offences. To do so, the probability of custodial sentence severity is modelled using multilevel Cox regression using data from online sentence transcripts. Findings contribute insights into how punishment is shaped by not only the presence of alcohol intoxication in offending but also in which contexts by highlighting the significant punitive effects of reference to concomitant drug use, the defendant drinking together with the victim and if the offence occurred in a private setting. This helps clarify complex considerations taken into account by sentencers when processing cases and the need for clearer guidance.